The Validity and Practicality of Journalistic Practice Learning Tools based on Project-Based Learning for Higher Education - Yusandra, Titiek Fujita; Fitri, Laila; Rinaldi, Rio (International Journal of Language Pedagogy, 2025)
This study aims to produce learning tools in the form of Semester Learning Plans, Course Learning Activity, and Journalism Practice Modules based on Project-Based Learning (PjBL) that are valid and practical. The method used is Research and Development (R&D) with a one group pretest-posttest design. The sample consisted of 20 students of the Indonesian Language and Literature Education Study Program at Universitas Bung Hatta and 10 students of the Universitas Muhammadiyah Sumatera Barat. Data were collected through an instrument in the form of a validation questionnaire reviewed by reviewers, experts (lecturers), and practitioners. The practicality questionnaire was filled out by lecturers and students, covering aspects of ease of use, time efficiency, and benefits. The results of the validation of the journalistic practice learning tools obtained an average validity score of 0.83 for Semester Learning Plans, 0.85 for Course Learning Activity, and 0.86 for the module. These scores indicate that the validity of the learning tools is in the very high category. The results of the practicality of the journalistic practice learning tools are in the very practical category. The average practicality scores of students towards Semester Learning Plans and modules were 86.1 and 83.1% respectively, while from lecturers it was 90.8% (Semester Learning Plans), 88.7% (Course Learning Activity), and 88.7% (Module). The research product, consisting of project-based learning tools for journalism practice, namely the Semester Learning Plan, Course Learning Activities, and Learning Modules based on Project-based Learning, demonstrated high levels of validity and practicality, indicating its suitability for implementation in higher education.